A history of missionary photography through the archives of the Société des missions évangéliques de Paris - Paris evangelical mission society (1880-1971) - (:unkn) unknown (My University, 2011)
In the missionary context, photography is sometimes used to serve the evangelization of the non-Christians. However, it is mainly circulated amongst the western Christians to inform them about the progress of the religious work.Built up between 1880 and 1971, the photographic collection of the Société des missions évangéliques de Paris (Paris evangelical missionary society or SMEP) was developed to meet the needs of the French Protestant missions. Through the study of its iconography and plastic qualities, as well as the study of its distribution, this research analyses the links between Christian mission and photography. It highlights how the picture is associated with the text and serves the missionary propaganda. It also reveals a historicity specific to the missionary photography which develops in three stages:- The exploration of the mission fields at the end of the 19th century, during which the missionaries intend to make an "inventory" of the African continent, - The development of the missionary work during the first half of the 20th century; the mission is then shown through its various activities and it gives to the converts a visual identity corresponding to the western Christian values,- The political independences during which the photographs display the disruption of the relations between local people and missionaries who look for new forms of action.The missionary photographs offer an original look at Africa by the Western countries and allow us to better understand the construction of the identity given to the Other through the image.
Keywords: African Research